2019
DOI: 10.4317/jced.55839
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cyclic fatigue lifespan between two different heat treated NiTi endodontic rotary instruments: WaveOne Gold vs EdgeOne Fire

Abstract: Background: Aim of this study is to investigate the cyclic fatigue resistance of the Gold treated WaveOne Gold and the Firewire treated EdgeOne Fire instruments. The null hypotesis was that there were no differences between the lifespan of Gold treated and FireWire treated instruments when subjected to cyclic fatigue tests. Material and Methods: 40 new NiTi instruments with a length of 25 mm were tested: 20 Wave One Gold Medium (WOG), tip size 35 and variable taper (Dentsply Maillefer, Ballaigues, Switzerland)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 34 publications
(33 reference statements)
0
41
2
Order By: Relevance
“…Different causes of fractures of endodontic instruments have been proposed by many authors and include operator experience [18,19], rotational speed [20,21], the number of uses [22], the number of rotations [23], pre-flaring [24], glide path [25], the angle and radius of the curvature [20,26], and the sterilization of instruments [27]. However, the influence of the frequency of pecking motion performed by the operator on the cyclic fatigue resistance of endodontic rotary instruments has not yet been analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different causes of fractures of endodontic instruments have been proposed by many authors and include operator experience [18,19], rotational speed [20,21], the number of uses [22], the number of rotations [23], pre-flaring [24], glide path [25], the angle and radius of the curvature [20,26], and the sterilization of instruments [27]. However, the influence of the frequency of pecking motion performed by the operator on the cyclic fatigue resistance of endodontic rotary instruments has not yet been analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, only 12% of published cyclic fatigue studies have used a dynamic fatigue device [30]. Most studies that have compared static and dynamic cyclic fatigue studies have concluded that the time to fracture of endodontic rotary instruments submitted to dynamic cyclic fatigue studies was approximately 20-40% higher than that found in static cyclic fatigue studies [26,[31][32][33][34][35]. Previous dynamic cyclic fatigue devices have been unable to accurately identify the causes of endodontic rotary instrument failures because of the absence of standardization of the axial direction of the pecking motion.…”
Section: Discussionmentioning
confidence: 99%
“…Several proprietary heat treatment applications have been developed. Studies have shown that thermal treatments (for files with the same geometry and design) enhance the cyclic fatigue lifespan while, at the same time, reducing the torsional resistance of a file [8][9][10]. Some studies have also compared heat-treated files and non-heat-treated files with different cross-sectional designs in cyclic fatigue tests, which demonstrate that heat treatment may not be the most influential parameter for flexural resistance [11].…”
Section: Introductionmentioning
confidence: 99%
“…Both of systems were reciprocating single-file and single-use systems. The WaveOne Gold is created using proprietary thermal processing obtained by heating the NiTi file and then cooling it slowly; different from production of M-Wire, a pre-manufacturing thermal processing, which is attributed to improvement instrument's elasticity [5]. The Reciproc Blue results from creative thermal processing that produce an instrument with a blue surface.…”
Section: Introductionmentioning
confidence: 99%